"A handshake across the Himalayas:" Chinese investment, hydropower development, and state formation in Nepal. Issue 3 (3rd May 2016) - Murton, Galen; Lord, Austin; Beazley, Robert
Abstract: This article examines contemporary patterns of Chinese infrastructure development in Nepal's Rasuwa District and the ways in which Nepali actors engage with Chinese investments to advance projects of state formation. Particularly in the wake of political volatility and natural disaster, Chinese interventions support the material and imaginative projects of a Nepalese state seeking stability, security, and economic growth. Long perceived as peripheral to the state center, Rasuwa is rapidly becoming central to Sino-Nepal relations, particularly in the context of bilateral investments in hydropower and transportation infrastructure. Drawing on data generated from 30 months of fieldwork in Nepal, we argue that Chinese development in Rasuwa: a) undergirds territorializing practices of the Nepalese state; b) represents a "gift of development" that connects Nepali ambitions of bikas (development) with Chinese anxieties over exile Tibetan populations; and c) reflects a strategic reorientation of geopolitical alliances between Nepal, China, and India. Challenging studies that depict Chinese development as an overwhelming extractive force, we instead show how small states like Nepal in fact use Chinese interventions to advance domestic projects of state formation and national security at home. On the basis of this study, we expand understandings about the place and priority of infrastructure in national state-making agendas, illustrate uneven local experiences with international development interventions, and highlight new configurations of Chinese investment and development abroad – characterized in Nepal as a "handshake across the Himalayas."